Coping with chronic illness - Moe, Barbara A. (New York Rosen Pub. Group, 1992)
Discusses chronic illness and its problems, with specific chapters on asthma, diabetes, epilepsy, cancer, cystic fibrosis, sickle cell anemia, and stress.
Includes bibliographical references (p. 165-171) and index.
Keywords: Chronic diseases -- Juvenile literature; Diseases; Counselor Education